2011
DOI: 10.1542/peds.2010-2257
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Development of Late-Preterm Infants: A Systematic Review

Abstract: CONTEXT: Late-preterm infants (LPIs) born at 34 to 36 weeks' gestation are increasingly regarded as being at risk for adverse developmental outcomes. To date, the early childhood development of LPIs has not been systematically considered. OBJECTIVE: To undertake a broad examination of literature relating to early childhood development at the ages of 1 to 7 years of LPIs born at 34 to 36 weeks' gestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
163
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 48 publications
3
163
0
4
Order By: Relevance
“…However, there is increasing concern about the risks of adverse outcome for late preterm neonates, with studies identifying an increased risk of neonatal morbidity 22 , rehospitalisation in early childhood 23 and academic difficulties in children at school age 24 . These risks are thought to be associated with both gestational age and biological factors associated with the preterm birth, including PPROM 25 , however, immediate delivery does not appear to improve outcomes in preterm neonates and may exacerbate the risks of prematurity because of birth in the absence of labor and earlier gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing concern about the risks of adverse outcome for late preterm neonates, with studies identifying an increased risk of neonatal morbidity 22 , rehospitalisation in early childhood 23 and academic difficulties in children at school age 24 . These risks are thought to be associated with both gestational age and biological factors associated with the preterm birth, including PPROM 25 , however, immediate delivery does not appear to improve outcomes in preterm neonates and may exacerbate the risks of prematurity because of birth in the absence of labor and earlier gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the risk of neonatal morbidities, moderately preterm-born children are also more likely to have developmental delays at preschool age. [7][8][9] Particularly in moderately preterm-born children, it remains unclear whether these neonatal morbidities are associated with the increased risk of developmental delay. 9 In the general population, male gender, small-for-gestational-age (SGA) status at birth, decreasing gestational age, and low maternal education increase the risk of developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Children born at these gestations are at higher risk for developmental delay, cognitive deficits, attention problems and special educational needs than their term-born peers. [2][3][4][5] These problems are evident in infancy and recent population-based studies have shown that children born LMPT are at twice the risk for neurodevelopmental disability compared with term-born controls at two years of age. [6] Developmental assessments in the early years are regarded as important for identifying children at risk and for targeting early intervention.…”
mentioning
confidence: 99%